2017
DOI: 10.1159/000477827
|View full text |Cite
|
Sign up to set email alerts
|

Synergic Impact of Vascular Calcification and Low Autonomic Tone in Mortality of Hemodialysis Patients

Abstract: Background: Both cardiovascular calcification and autonomic dysfunction are frequently encountered in hemodialysis patients. We aimed to investigate the relationship between cardiovascular calcification and heart rate variability (HRV) and their influence on long-term outcome. Methods: Seventy-eight hemodialysis patients underwent echocardiogram and radiography of the pelvis and hands to identify valvular and vascular calcification. HRV was evaluated using a commercial machine. Results: Based on the average, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(33 reference statements)
1
4
0
1
Order By: Relevance
“…Hemoglobin level was positively correlated with change in LF after HD in patients ≥65 years old in the present study. In line with our findings, a positive correlation between hemoglobin and LF was shown in HD patients ( Ng et al, 2017 ). This implied that better sympathetic compensation occur as a result of fluid removal during HD in patients with better hemoglobin level.…”
Section: Discussionsupporting
confidence: 92%
“…Hemoglobin level was positively correlated with change in LF after HD in patients ≥65 years old in the present study. In line with our findings, a positive correlation between hemoglobin and LF was shown in HD patients ( Ng et al, 2017 ). This implied that better sympathetic compensation occur as a result of fluid removal during HD in patients with better hemoglobin level.…”
Section: Discussionsupporting
confidence: 92%
“…VC may impact other physical pathological factors in CKD patients, bringing in high risk of cardiovascular mortality. VC was suggested to be related to autonomic dysfunction and arterial stiffness, both of which may influence the variability of blood pressure (BPV). BPV refers to the fluctuations of blood pressure (BP).…”
Section: Introductionmentioning
confidence: 99%
“… Zhang, et al, 2013 ). Ng et al (2017) reported that calcification of hand artery (HA) was associated with autonomic dysfunction, the patients with lower autonomic tone and severe HA calcification had the highest mortality rate. Fadaee et al (2017) found that oxidative stress is significantly and independently associated with decreased HRV in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%